GUT–BRAIN AXIS: PHYSIOLOGICAL MECHANISMS LINKING GASTROINTESTINAL FUNCTION AND MENTAL HEALTH (Asian Journal of Medical Research and Health Sciences, 2026)
The gut–brain axis represents a proper complex bidirectional communication network integrating neural, endocrine, immune, and the metabolic pathways between the gastrointestinal tract and the central nervous system. Exceptional evidence has been demonstrated that gastrointestinal activities and gut microbiome possess a highly notable impact on emotional control, cognitive capacity, and psychiatric vulnerability. This paper presents an overview of the existing mechanistic research investigations of the physiological processes involved in the interrelationship between the operation of gastrointestinal tract and mental health condition. The review describes the neural pathways using the aid of vagus nerve and enteric nervous system, endocrine signaling via hypothalamic-pituitary-adrenal axis, immune-inflammatory signaling cascades, and microbial metabolite signaling structural models such as short-chain fatty acids, tryptophan metabolites, and neurotransmitters. The methodology systematic approach was applied to study the data of peer-reviewed experimental and clinical trials that were recorded in the international databases. Findings indicate that dysbiosis, intestinal permeability, neurodevelopmental disorders and neurodegenerative mechanisms are associated with depression, anxiety disorders, neurodevelopmental disorders, and stress-induced adaptations in gastrointestinal motility. The neurobehavioral effects of interventions of microbiota modulation, including probiotics, dietary fibers supplement as well as fecal microbiota transplant, have been observed although there remains clinical variability. The results highlight the compensatory nature of the gut-derived signaling on the neurochemical balance, synaptic plasticity, and stress responsiveness. The topic does not only evaluate the translational implications, but also identifies methodological constraints of existing literature, and offers future opportunities of biomarkers and precision psychiatry. The paper ends by concluding that the gut-brain axis is a fundamental physiological mechanism of connecting somatic, and mental health and hence the implication of the same on therapeutic innovation and interdisciplinary research.